STRATEGI PEMASARAN MELALUI KOPERASI PETANI IKAN LELE DI GUNUNG SINDUR KABUPATEN KABUPATEN BOGOR: Strategi Pemasaran melalui Koperasi Petani Ikan Lele di Gunung Sindur Kabupaten Kabupaten Bogor - Utju, NINING LATIANINGSIH; Iis Mariam; Dewi Winarni (Politeknik Negeri Medan, 2020)
The implementation of community service will be held in the village of Curug District Mount Sindur Bogor Regency Government - West Java this year is the result of community service program Appropriate Technology Service KemenristekBrin. Community service is a manifestation of the implementation of The Tri Dharma of Higher Education which must be carried out by lecturers assisted by administrative staff and students. Community service is to establish cooperatives for catfish farmers who have difficulty for post-harvest catfish, because the price is in addition to falling and caused by the Covid 19 Pandemic, so that catfish farmers experience a decrease in income. With the existence of containers in the form of cooperatives are expected to increase people's income, especially by processing catfish into food that can increase income. The method used is to provide briefing in theory and practice. The community service activities provide training on the establishment of cooperatives, product marketing is carried out online (social media marketing), compiling financial reports cooperatives fish farmers in the village Curug District Mount Sindur Bogor Regency. This devotional activity was carried out on November 10, 2020, after the implementation of this service was completed monitoring the results of community service activities whether it has been implemented in accordance with applicable procedures. Community service activities are to provide knowledge to Catfish Farmers who are in the village curug District Mount Sindur, Bogor district in order to be able to solve with a solution that was years earlier, namely marketing its products using social media marketing, providing solutions that can be implemented by catfish farmers and can communicate with the community and village officials in running their businesses in the form of cooperatives using Social media properly and correctly , to respond to the situation during this pandemic